Validated Prospective Assessment of Quality of Life After Robot-Assisted Laparoscopic Prostatectomy: Beyond Continence and Erections. Issue 3 (31st May 2019) - Albisinni, Simone; Aoun, Fouad; Quackels, Thierry; Assenmacher, Grégoire; Peltier, Alexandre; van Velthoven, Roland; Roumeguère, Thierry
Continence and erectile function represent major concerns after robot-assisted laparoscopic prostatectomy (RALP), although the analysis of only these results may underestimate the impact of surgery on quality of life (QoL). The aim of the study is to prospectively analyze QoL after RALP according to the validated European Organization for Research and Treatment of Cancer Quality of Life Questionnaire prostate cancer–specific module (EORTC-QLQ-PR25) and C30 and explore risk factors for the deterioration of QoL after surgery. A total of 584 patients undergoing RALP were prospectively enrolled. QoL was assessed with the validated EORTC-QLQ-PR25 and C30. Differences across QoL items were assessed via Wilcoxon rank-sum test and associations between risk factors and QoL scores were tested via univariate and multivariate linear regression analyses. All items of the PR25 questionnaire showed a significant deterioration at 1 month after RALP and began to normalize 3 months after surgery. At 24 months follow-up, urinary, bowel, and sexual activity scores were not significantly different from preoperative scores, while incontinence aid, treatment-related symptoms, and sexual functioning remained significantly worse. Preoperative sexual activity was more important in determining 3-month sexual outcomes than preoperative 5-item version of the International Index of Erectile Function (IIEF-5) or nerve-sparing approach. An overall return to preoperative QoL was registered at 3 months after RALP in global and physical QoL, and most important, global, physical, social, and role-functioning QoL scores were improved at 12 and 24 months compared to preoperative scores. In this prospective study, detailed data on QoL are reported via the EORTC-PR25 and C30 questionnaires. While urinary, bowel, and sexual activity scores return to baseline values 24 months after surgery, incontinence aid, treatment-related symptoms, and sexual functioning may remain significantly deteriorated. Larger studies are needed to validate these findings.